Types of responsibility for violation of fi nancial legislation in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
The article discusses the types of legal liability in the fi eld of fi nancial law. Given the basic concepts and briefl yanalyzed the system of norms of law enforcement relations for the Institute of responsibility.Key words: Financial legislation, administrative liability, criminal liability.